KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA KERJA POSITIF (Studi Deskriptif kualitatif di SMP Negeri 3 Baleendah Kabupaten Bandung) - Hendi Suhendraya Muchtar; Helmawati; Rina Nuraeni; Yulidar; Winda Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Effective leadership in schools significantly impacts the quality of education, where the school principal plays a crucial role in establishing the vision, mission, and objectives. This study explores the application of transformational leadership at SMP Negeri 3 Baleedah and its impact on a positive work culture. Through a qualitative approach, data were collected from interviews, questionnaires, and documentation involving the principal and teachers. The findings indicate that the application of transformational leadership, such as building a clear vision and encouraging collaboration, successfully enhances motivation, work enthusiasm, and communication among teachers. However, challenges such as pressure to perform and uncertainty during changes persist. The results of this study are expected to provide insights for school principals and education managers in formulating better strategies to improve the work environment in schools and serve as a reference for developing leadership policies in other educational institutions.